INOVAREA-COMPONENTA PRINCIPALA A TRIUNGHIULUI CUNOASTERII - Radu Ioana (Annals of the University of Oradea: Economic Science, 2012)
Science has begun to play an increasing role in industrial development not only as a major source of knowledge for new technological activities or scientointensive industries (medicine industry, chemistry, electronics), but also as essential input in testing, evaluation and quality control. Innovation is one of the activities that can generate economic and social progress. Therefore, this paper also approaches the significance of innovative information dissemination, as well as the objectives of this activity in view of the EU Member States. The European Union has prepared two funding programs for innovation activity, Europe 2020 and Horizon 2020.